2022
DOI: 10.1002/pen.26210
|View full text |Cite
|
Sign up to set email alerts
|

Effect of infill pattern on the mechanical properties of polydopamine‐coated polylactic acid orthopedic bone plates developed by fused filament fabrication

Abstract: Distal fractures are the most commonly experienced type of fractures that require fixation of bone plates for healing of fractured bones. Poly Lactic Acid (PLA)‐based bone plates are porous and light in weight. However, they lack mechanical properties that limit their application in biomedical field. Polydopamine coating has been witnessed to undergo covalent interactions, enhancing the mechanical properties of the substrate. The present study is based on the fabrication of PLA‐based bone plates using Fused Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Meanwhile, PNCs have been fabricated with enhanced thermal and electrical conductivity, improved mechanical and thermal expansion, and increased fire retardancy for automotive, oil and gas, and other versatile applications 137–207 . Finally, it is emphasized that 3‐DPT and 4‐DPT are innovative processing technologies, presenting the future route of the manufacturing sector 208–244 …”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, PNCs have been fabricated with enhanced thermal and electrical conductivity, improved mechanical and thermal expansion, and increased fire retardancy for automotive, oil and gas, and other versatile applications 137–207 . Finally, it is emphasized that 3‐DPT and 4‐DPT are innovative processing technologies, presenting the future route of the manufacturing sector 208–244 …”
Section: Discussionmentioning
confidence: 99%
“…Several key findings from studies in FDM and 3D printing parameters include: increasing bed temperature to 160°C and reducing PS to 60 mm/s, as reported by Miazio (2019), Wang et al (2017), results in strong bonding and PLA fiber diffusion. Sharma et al (2022b) investigated various infill patterns for biomedical implants in FDM. The gyroid pattern provided enhanced structural stability and minimal voids, improving biomedical bone plate properties.…”
Section: Introductionmentioning
confidence: 99%
“…PDM is deposited on PLA through direct immersion technique that involves selection of coating parameters. 22 From the reported literatures 20,21,23,24 on mechanical testing of PDM-coated PLA structures in 1 mg/mL and 2 mg/mL concentrated solutions, it was ascertained that increase in coating solution concentration enhanced the mechanical characteristics of the coated structures. The previous studies have reported coating of PLA structures for submersion time ranging from 4 to 24 h 20,21,[23][24][25] that resulted in deposition of thick coating at longer submersion times.…”
Section: Introductionmentioning
confidence: 99%
“…PDM is deposited on PLA through direct immersion technique that involves selection of coating parameters 22 . From the reported literatures 20,21,23,24 on mechanical testing of PDM‐coated PLA structures in 1 mg/mL and 2 mg/mL concentrated solutions, it was ascertained that increase in coating solution concentration enhanced the mechanical characteristics of the coated structures.…”
Section: Introductionmentioning
confidence: 99%